The Role of Taste Receptor mTAS1R3 in Chemical Communication of Gametes - Frolikova, Michaela; Otcenaskova, Tereza; Valasková, Eliska; Postlerova, Pavla; Stopkova, Romana; Stopka, Pavel; Komrskova, Katerina (International journal of molecular sciences, 2020)
Fertilization is a multiple step process leading to the fusion of female and male gametes and the formation of a zygote. Besides direct gamete membrane interaction via binding receptors localized on both oocyte and sperm surface, fertilization also involves gamete communication via chemical molecules triggering various signaling pathways. This work focuses on a mouse taste receptor, mTAS1R3, encoded by the Tas1r3 gene, as a potential receptor mediating chemical communication between gametes using the C57BL/6J lab mouse strain. In order to specify the role of mTAS1R3, we aimed to characterize its precise localization in testis and sperm using super resolution microscopy. The testis cryo-section, acrosome-intact sperm released from cauda epididymis and sperm which underwent the acrosome reaction (AR) were evaluated. The mTAS1R3 receptor was detected in late spermatids where the acrosome was being formed and in the acrosomal cap of acrosome intact sperm. AR is triggered in mice during sperm maturation in the female reproductive tract and by passing through the egg surroundings such as cumulus oophorus cells. This AR onset is independent of the extracellular matrix of the oocyte called zona pellucida. After AR, the relocation of mTAS1R3 to the equatorial segment was observed and the receptor remained exposed to the outer surroundings of the female reproductive tract, where its physiological ligand, the amino acid L-glutamate, naturally occurs. Therefore, we targeted the possible interaction in vitro between the mTAS1R3 and L-glutamate as a part of chemical communication between sperm and egg and used an anti-mTAS1R3-specific antibody to block it. We detected that the acrosome reacted spermatozoa showed a chemotactic response in the presence of L-glutamate during and after the AR, and it is likely that mTAS1R3 acted as its mediator.
Keywords: Receptors, G-Protein-Coupled; exprese genu; interakce spermie a vajíčka; Gene Expression; RNA, Messenger; Male; Cell Communication; L-glutamate; acrosome reaction; buněčná diferenciace; mouse; Spermatozoa; mužské pohlaví; Glutamates; mTAS1R3 receptor; Sperm-Ovum Interactions; sperm; gamete; mezibuněčná komunikace; glutamáty; Animals; chemotaxis; ženské pohlaví; zvířata; TAS1R family; receptory spřažené s G-proteiny; spermie; myši; Mice; Chemotaxis; Female; chemoattractant; messenger RNA; chemotaxe; Cell Differentiation